1990
DOI: 10.20965/jrm.1990.p0308
|View full text |Cite
|
Sign up to set email alerts
|

A New Design of a 6-DOF Parallel Robot

Abstract: This paper presents a six-degree-of-freedom parallel robot which has been recently designed. The design is based on a three-degree-of-freedom parallel robot called DELTA which was designed in Switzerland by EPFL. First, we give equations corresponding to different models of the DELTA robot: forward and inverse kinematics as well as inverse dynamics. An important feature of our method in deriving these models is to use a “good” set of parameters in order to simplify the equations. Then, in an attempt to extend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Three 6-RUS manipulators include Hunt type (Hunt, 1983), Hexa (Pierrot, 1990) and a manipulator named Zamanov type by the authors as it was proposed by Zamanov (Merlet, 2006) Schematic of a manipulator is shown in Figure 2 to determine different aspects. According to the Figure 2, B and P are center of coordinate connected to fixed and mobile platform, respectively.…”
Section: Description Of Notation For 6-rusmentioning
confidence: 99%
“…Three 6-RUS manipulators include Hunt type (Hunt, 1983), Hexa (Pierrot, 1990) and a manipulator named Zamanov type by the authors as it was proposed by Zamanov (Merlet, 2006) Schematic of a manipulator is shown in Figure 2 to determine different aspects. According to the Figure 2, B and P are center of coordinate connected to fixed and mobile platform, respectively.…”
Section: Description Of Notation For 6-rusmentioning
confidence: 99%
“…Few of them have also applied this method to solve FKP of other parallel robot (Ghobakhlo et al, 2005), (Sadjadian et al, 2005). In this chapter, we focus on HEXA parallel robot, first presented by Pierrot (Pierrrot et al,1990), whose platform is coupled to the base by 6 RUS-limbs, where R stands for revolute joint, U stands for universal joint and S stands for spherical joint (see Fig. 2).…”
Section: Review Of Forward Kinematics Problem Of Parallel Robotmentioning
confidence: 99%
“…Complete description of HEXA robot is presented in Section 2. The solution of IKP of HEXA was first presented in (Pierrrot et al, 1990) by F. Pierrrot who solved the system of nonlinear equations and obtained a unique solution for the problem. A numerical solution for FKP of HEXA parallel robot was presented by J.P. Merlet in (Merlet, 2001).…”
Section: Review Of Forward Kinematics Problem Of Parallel Robotmentioning
confidence: 99%
“…In addition, distinct arrangements of the joints and legs may lead to very simplified direct kinematics, higher stiffness, or higher resolution. Most examples of 6-DOF fully-parallel manipulators may be classified by the type of their six identical serial chains being RRPS, RRRS, or PRRS (Bonev, 1998;Briot et al, 2009;Carbonari et al, 2013;Isaksson et al, 2012;Liu et al, 2002;Merlet, 2000;Pierrot, 1990;Uchiyama, 1993;Zhang, 2010). In this representation, RR stands for a universal joint (U), sometimes PR stands for a cylindrical joint (C), P for a prismatic joint, R for a rotary joint, S for a spherical joint, and an underlined letter designates an actuated joint.…”
Section: Introductionmentioning
confidence: 99%